The effect of low-intensity interval training (HIIT) aerobic exercises on developing certain physical and functional variables and performance in the 1500-meter run. - Hakim, Dr. Shino Zahir; Nouri, Asst.L. Saman Faiq; Mohammed, Asst.L. Ribwar Othman (Sulaimani Journal for Humanities, 2026)
Athletics is an activity that is influenced by all elements of physical fitness. Specialization within athletics leads to an improvement in physical and physiological aspects. Middle-distance running is one such athletics event, requiring specific development of certain fitness components and their associated energy systems to achieve physiological adaptation of the functional systems necessary for performance and endurance during training and competition, ultimately aiming for the best possible time. The research problem lies in the insufficient attention given to organizing and selecting the correct and appropriate methods for developing physical and functional efficiency, particularly through the use of low-intensity interval training (HIIT) for aerobic endurance. The research aims to identify the effect of using HIIT for low-intensity interval training on certain physical and functional variables and performance in the 1500-meter race among the participants in the study. The researchers used an experimental approach with a single-group experimental design. The research population consisted of eight (8) young 1500-meter runners from clubs in Sulaymaniyah Governorate, representing 100% of the original research population. The researchers developed aerobic exercises using low-intensity interval training. The training program comprised 16 training sessions, with three sessions per week. Post-tests were conducted to analyze the research variables and verify the hypotheses. The researchers used the SPSS statistical package. The researchers concluded that using low-intensity interval training positively impacted the development of physical variables, including speed endurance and strength endurance, and improved 1500-meter running performance. Keywords: Aerobic exercises, low-intensity interval training, physical and functional variables, 1500m running.